Atomic Layer Deposition in a Metal–Organic Framework: Synthesis, Characterization, and Performance of a Solid Acid - Rimoldi, Martino; Bernales, Varinia; Borycz, Joshua; Vjunov, Aleksei; Gallington, Leighanne C; Platero-Prats, Ana E; Kim, I. S; Fulton, John L; Martinson, A. B. F; Lercher, Johannes A; Chapman, Karena W; Cramer, Christopher J; et al. (Chemistry of materials, 2017)
NU-1000, a zirconium-based metal–organic framework (MOF) featuring mesoporous channels, has been postsynthetically metalated via atomic layer deposition in a MOF (AIM) employing dimethylaluminum iso-propoxide ([AlMe2O i Pr]2, DMAI), a milder precursor than widely used trimethylaluminum (AlMe3, TMA). The aluminum-modified NU-1000 (Al-NU-1000) has been characterized with a comprehensive suite of techniques that points to the formation of aluminum oxide clusters well dispersed through the framework and stabilized by confinement within small pores intrinsic to the NU-1000 structure. Experimental evidence allows for identification of spectroscopic similarities between Al-NU-1000 and γ-Al2O3. Density functional theory modeling provides structures and simulated spectra, the relevance of which can be assessed via comparison to experimental IR and EXAFS data. The catalytic performance of Al-NU-1000 has been benchmarked against γ-Al2O3, with promising results in terms of selectivity.